The Relation between Preoperative Impedance Audiometry Findings andPostsurgical Outcomes of Tympanoplasty (The Planet, 2024)
Introduction: The success of tympanoplasty surgery depends significantly on Eustachian tube function, yet the predictive value of preoperative impedance audiometry remains incompletely understood. This study investigates the relationship between preoperative impedance audiometry findings and surgical outcomes in tympanoplasty patients. Methods & Materials: In this prospective observational study, we evaluated 60 patients (34 females, 26 males) aged 18-58 years who underwent tympanoplasty between January 2023 and December 2023. All patients underwent comprehensive preoperative assessment including impedance audiometry to evaluate Eustachian tube function. Surgical outcomes were assessed through graft uptake status and audiological parameters at 3 and 6 months postoperatively. Results: The overall graft uptake success rate at 6 months was 83.3%. Patients with good Eustachian tube function showed significantly higher success rates (92.1%) compared to those with poor function (50%). The mean air-bone gap improved from 28.5 ± 8.4 dB preoperatively to 15.2 ± 7.6 dB postoperatively (p < 0.001). Multiple regression analysis identified preoperative Eustachian tube function as the strongest predictor of surgical success (OR = 3.28, 95% CI: 1.86-5.79, p < 0.001), followed by perforation size (OR = 1.94, 95% CI: 1.12-3.36, p = 0.018). Conclusion: Preoperative impedance audiometry provides valuable prognostic information for tympanoplasty outcomes. Good Eustachian tube function correlates strongly with successful graft uptake and hearing improvement. These findings support the routine use of impedance audiometry in preoperative assessment to optimize patient selection and surgical planning in tympanoplasty.
Keywords: Impedance audiometry; Eustachian tube function; Tympanoplasty; Surgical outcome; Middle ear pressure; Graft uptake